Comparative Study between Two Fractions of 9Gy & Three Fractions of 7Gy High Dose Rate Brachytherapy Following Concurrent Chemo Radiotherapy in Patients with Locally Advanced Carcinoma of Uterine Cervix - Ferdous, Jannatul; Hossain, Altaf; Sultana, Sarowat; Akter, Touhida; Haque, M Nizamul (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Traditionally, a judicious combination of external beam radiotherapy (EBRT) and intracavitary brachytherapy (ICBT) is the widely accepted primary modality of treatment for locally advanced carcinoma of the cervix. Although the recommendation ofAmerican Brachytherapy Society is <7.5 Gyfor individual fraction and four to eight should be the range of fractions; however, literature showed high dose rate (HDR) brachytherapy of two fractions of 9Gyresults in acceptable toxicity without compromising the local control. Methods: This was a Prospective Quasi-Experimental study, conducted in Department of Radiation Oncology, National Institute of Cancer Research and Hospital, Mohakhali, Dhaka from July 2018 to June 2019. Patients with Clinically diagnosed and histopathologically proven squamous cell carcinoma of uterine cervix in locally advanced stage (FIGO stage IIB to IVA) were selected. Total 60 patients were enrolled according to selection criteria and allocated in to group. Both arm was received 50Gy EBRT in 25 fractions with concurrent inj.Cisplatin 40 mg/m2 weekly. Then Arm A was given HDR Brachytherapy 9Gy in each fraction for 2 fractions and Arm B was given HDR Brachytherapy 7Gy in each fraction for 3 fractions. Then treatment responses, locoregional control of disease and acute toxicities were compared between groups. Result:Follow up at 6 months after completion of treatment, complete remission was 90% and 86% respectively for arm A and arm B. The overall complete response was 88%. The common toxicities associated with treatment were bladder and rectal toxicities, skin reaction, small bowel toxicity and haematologic complications which were managed well. During follow up after 6 months, 3 patients in arm A and 2 patients in arm B developed grade II bladder toxicities and only 2 patients in arm A developed rectal grade II toxicities, but there was no rectal toxicity in arm B. Conclusions: Present study showed that a total dose of 18 Gy ICRT in two fractions of 9 Gy over 2 weeks is equally effective in short term local control with acceptable toxicities in comparison with a total dose of 21 Gy in three fractions of 7 Gy ICRT. J Bangladesh Coll Phys Surg 2024; 42: 49-56